ХРИСТИЙН ШАШНЫ НЭСТОРЫН УРСГАЛД ХОЛБОГДУУЛЖ БОЛОХ ГУРВАН ДУРСГАЛ - Алдар Ю. Болдбаатар (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2002)
A inscription of Ulaan tolgoi is Syriac inscriptions, which used by nestorians in Central Asia. The first Syriac inscription of Ulaan tolgoi is one of most important historical object of spread of ancient nestorian religion and inscription, because researchers could not read the inscription. We have a hypothesis that stone statue of Dayan hero and monument of Daagan stone were built by nestorians. We believe, the Over mentioned three are very important objects of influence of nestorians in history and culture of ancient and middle age Mongolia and Central Asia.